La educomunicación en la televisión lojana: UV televisión, como proceso de formación en la juventud que se educa en el colegio Manuel Cabrera Lozano anexo a la Universidad Nacional de Loja, considerando las edades entre 13 y 17 años de la ciudad de Loja” período enero-mayo 2013. Propuesta alternativa - Llanes Armijos, Gabriela Fernanda (2014)
The TV comes in Ecuador as the need to be informed of everything that happens in the country and the world, is how many have described as a need that is part of the family, the Ecuadorian television has been characterized by entertaining for many years to small, large programs either sensational or as some educational cases. Media education is referred to as a field of interdisciplinary study that addresses the theoretical and practical two historically separate disciplines dimensions: education and communication, thereby aim was raised investigate whether the means of Loja media contribute to intellectual Social and academic training youth, as well as specific objective set out to create an educational and entertainment for young people who have the duration of 26 minutes will be issued on Wednesdays between the hours of 15:00 to 15:30 program. The lack of educational programs or media education unprecedented makes them come to the internet to the famous social networks, where not only disclosed in the network everything that happens in your daily life but find distraction for development employed materials, methods, techniques and tools that allowed accurately investigate basis of the results, taking as research subjects both youth 13-17 years of college Manuel Cabrera Lozano and the respective parents of students, of which some conclusions and recommendations were obtained. In Loja television has a great lack of educational programs this is because these have a high cost of production or youth do not feel more attracted to observe, which makes managers lose interest in transmitting these programs because have a shortage of hearing, and the absence of these makes you feel the need to experience new things that do not contribute to its development, and in the same school did not have a schedule or workshop where we speak of the consequences as lack of creativity and communication brings much television watching. It was concluded that the UV channel lacks an educational TV programming for education, training, guidance and wholesome entertainment.